Metodologi Hermeneutika Hassan Hanafi - Khoirul Fatih, Moh (Program Studi Ilmu Al Quran dan Tafsir Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2023)
As a methodology for interpreting the Qur'an, hermeneutics consists of three models, objective hermeneutics, subjective hermeneutics and liberation hermeneutics. Speaking of Hassan Hanafi, of course, cannot be separated from the framework of occidentalism that he echoes as a form of response to orientalism thought developed by Western thinkers. Hasan Hanafi carries three extraordinary programs that are oriented towards the reconstruction of an liberated and independent Islamic culture. With his first program, Mawqifuna min al-turats al-qadim, Hasan Hanafi wants to reform Islamic thought by revitalizing classical turats and reconstructing them so that they are not obsolete and useful for today. The procedure of interpretation offered by Hasan Hanafi, that before interpreting a text, an interpreter must first analyze his own experience to bring up interests, motivations, and social positions. With its realist, thematic, temporal, transformative and experimental character, the interpretation methodology offered by Hasan Hanafi, in addition to showing the frame of renewal of his thinking, also appears to have been led to legitimize his leftist renewal project. In this interest bias is the occurrence of contradictions in hermeneutical thinking. On the one hand, turning the textualist paradigm of classical hermeneutics into a realist paradigm, while on the other hand, the objective scientific orientation of modern Qur'anic hermeneutics is returned to a subjective orientation as in classical hermeneutics. In turn, it can be concluded that the phenomenological and Marxist approaches with the main characteristics of inter-class conflict analysis in society, are so prominent even though they are clad under the pretext of asbab al nuzul and masalih al ummah theories.